Exposição subcrônica de ratos wistar jovens a dose baixa de chumbo induz déficits locomotores e alterações morfológicas associados a estresse oxidativo e disfunção sináptica - PENHA, Luana Ketlen Reis Leão da (Universidade Federal do Pará, 2019)
Lead (PB) is a heavy metal, which can be utilized in the production of several compounds. The main route of human exposure is through the consumption of contaminated food or water, and once absorbed, about 99% of the circulating lead spreads to soft tissues, teeth, bones and brain. In the Central nervous system (CNS), several studies have demonstrated deficits in learning capacity, cognition and intellectual development in humans exposed to lead during a given period of life. However, it is poorly understood the mechanisms of action involved with the toxicity of Pb. From this, this study aimed to evaluate the exploratory, motor and tissue effects induced by the subchronic exposure of young wistar rats to 50 mg/Kg of lead, associated with possible mechanisms of action. Male Wistar rats were exposed for 55 days at a dose of 50mg/Kg of Pb per gavage, and the control animals received distilled water. The open field, inclined plane and route-rod tests were performed for locomotor evaluation. Staining was performed with Hematoxylin and Eosin, as well as immunohistochemistry for the quantification of mature neurons, myelin sheath and synaptic vesicles. To evaluate the protein expression, the Proteomic profile was performed. The statistical analysis was performed by Student's T-Test, being considered significant p < 0.05. After we observed lead deposition only in the cerebellum, it was possible to characterize exploratory and motor deficits in the rats exposed to lead, and we observed a decrease in the number of Purkinje cells, as well as mature neurons, reduction of vesicles synaptic and decreased myelin sheath. In the evaluation of oxidative stress induction, it was possible to evaluate the increase of MDA and nitrite only in the motor cortex. And in the evaluation of protein expression, both regions presented alterations in proteins responsible for the release process of neurotransmitters, as well as receptors and second messengers, and also proteins involved in the process of apoptose. Thus, we conclude that the subchronic exposure to low Pb dose of young Wistar rats promoted locomotor and histological tracings, associated with induction of oxidative stress, alterations in the process of cell signaling, as well as death by apoptosis.